Impact of botanical fermented foods on metabolic biomarkers and gut microbiota in adults with metabolic syndrome and type 2 diabetes: a systematic review protocol - Miin Chan; Helen Baxter; Nadja Larsen; Lene Jespersen; Elif I Ekinci; Kate Howell (BMJ Open)
Introduction Dysfunctional gut microbiota is a common finding in patients with metabolic syndrome (MetS) and type 2 diabetes mellitus (T2DM). Recent clinical trials have assessed whether botanical fermented foods (BFFs) have beneficial effects on metabolic biomarkers, inflammatory markers and gut microbiota. The aim of this review is to critically evaluate all randomised controlled trials (RCTs) of BFF for evidence of impact on the outcome measures of these disease states.Methods and analysis Four electronic databases (Embase, MEDLINE, CENTRAL and Google Scholar) as well as the grey literature will be searched from inception to present without language or publication status restrictions applied. Eligible RCTs which have enrolled adult participants with T2DM, any MetS components or combinations of these components, treated prophylactically or therapeutically with any botanical fermented food intervention, compared with a control group (no intervention, placebo or active control) will be assessed. Primary outcomes are related to the target conditions, including metabolic biomarkers, inflammatory markers and gut microbiota composition/function. Using Covidence, two independent investigators will conduct title and abstract screening, followed by full-text screening to identify appropriate studies. Methodological quality of the trials will be assessed using the Cochrane risk of bias assessment tool. Findings will be summarised with a narrative synthesis of the differences between included studies. A meta-analysis will be conducted if sufficient data are obtained.Ethics and dissemination Ethical approval is not required as primary data will not be collected. Results will be disseminated through peer-reviewed publication, conference presentations and press.PROSPERO registration number CRD42018117766